2015
DOI: 10.17221/5/2015-swr
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic fertilizers on soil organic carbon and risk trace elements content in soil under permanent grassland

Abstract: Karabcová H., Pospíšilová L., Fiala K., Škarpa P., Bjelková M. (2015): Effect of organic fertilizers on soil organic carbon and risk trace elements content in soil under permanent grassland. Soil & Water Res., 10: 228-235.The effect of different kinds of organic matter inputs on elemental composition, content, and quality of humic substances was studied on permanent grassland during 2008-2013. The experiment included two organic fertilizer types -compost and slurry, both with the range of stocking rates 0.9, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As a result, the soil becomes more susceptible to various forms of degradation, including acidification, wind and water erosion, low water retention, and pedocompaction. Bramble et al (2024), Karabcová et al (2015), and Pospíšilová et al (2011) discussed the opposite effect of fertiliser on SOM, where fertiliser positively increases plant production but reduces species diversity in grassland. Simiraly to us, they demonstrated that SOM accumulation in temperate grasslands is affected by management practices and fertilisation.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the soil becomes more susceptible to various forms of degradation, including acidification, wind and water erosion, low water retention, and pedocompaction. Bramble et al (2024), Karabcová et al (2015), and Pospíšilová et al (2011) discussed the opposite effect of fertiliser on SOM, where fertiliser positively increases plant production but reduces species diversity in grassland. Simiraly to us, they demonstrated that SOM accumulation in temperate grasslands is affected by management practices and fertilisation.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the discussed factors of grassland degradation, it should be emphasised that studies conducted by various authors prove that there is a positive relationship between the SOC content in grassland soils and their pH [KARABCOVÁ et al 2015], the state of humidity [KERR, OCHSNER 2020;TIAN et al 2016], and the level of fertilisation [VARGOVÁ et al 2020].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the discussed factors of grassland degradation, it should be emphasized that studies conducted by various authors prove that there is a positive relationship between the Corg content in grassland soils and their pH [46], the state of humidity [47,48], and the level of fertilization [49].…”
Section: [Table 13]mentioning
confidence: 99%